DAYA HAMBAT SARI DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) TERHADAP PERTUMBUHAN BAKTERI ESCHERICHIA COLI DAN Staphylococcus aureus - Indriati, Gustina; Agustina, Agustina; Widiana, Rina (IAIN Batusangkar, 2012)
Sirih merah (piper crocatum ruiz & pav) has been used, since ancient society, as drugs. The chemical compounds contained in red betel are as antibacterial, the compounds are: flavonoids, alkaloids. tannins and essential oils. The research has been conducted in order to determine the inhibition of red betel leaf extract (piper crocatum ruiz & pav) on the growth of the bacteria Escherichia coli and staphylococcus aureus. This study uses RAL with 6 treatments and 3 replications: A treatment (red betel leaf extract 10%), B (red betel leaf extract 20%), C (red betel leaf extract 30%), D (red leaf extract 40%) , E (red betel leaf extract 50%) and F (amoxicilin 10%) as controls. The results showed no real influence with inhibition diameter on treatment A (6.69 mm), treatment B (8.88 mm), treatment C (7.76 mm), treatment D (9.53 mm), treatment E (12 , 79mm) and treatment F (9.45 mm). From staphylococcus aureus it was obtained significant results with a diameter of inhibition in treatment C (7.70 mm), treatment A (8.22 mm), treatment D (8.58 mm), treatment B (9.53 mm), treatment E (10.39 mm ) and treatment F (17.59 mm). The red betel leaf extract was able to inhibit the growth of bacteria Escherichia coli and staphylococcus aureusKey words: Sirih merah, Escherichia coli, Staphylococcus aureus